Roar of the beast - Sell, Chad (New York Alfred A. Knopf, 2021)
When Elijah and Vijay are harassed by neighborhood teens, Vijay sinks into depression and renounces his character, the Beast. Nate, aka the Prince, is convinced that a terrible monster is invading the Cardboard Kingdom and will do whatever it takes to stop it. At the same time, Alice is working on a secret project that has her pushing the rest of the kingdom away. As the group wrestles with their fears and their friendships, they have to decide if these challenges will create a schism in their community or make the Cardboard Kingdom stronger.
"This is a Borzoi Book published by Alfred A. Knopf"--Colophon.
"RH Graphic"--Jacket.
School Library Journal
HL 160
3.0
4-7
Keywords: Imagination in children -- Comic books, strips, etc -- Juvenile fiction; Costume -- Comic books, strips, etc -- Juvenile fiction; Neighborhoods -- Comic books, strips, etc -- Juvenile fiction; Neighbors -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Bullying -- Comic books, strips, etc. -- Juvenile fiction; Monsters -- Comic books, strips, etc. -- Juvenile fiction; Imagination -- Comic books, strips, etc. -- Fiction; Costume -- Comic books, strips, etc. -- Fiction; Neighborhoods -- Comic books, strips, etc. -- Fiction; Neighbors -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Bullies -- Comic books, strips, etc. -- Fiction; Monsters -- Comic books, strips, etc. -- Fiction; Imagination -- Comic books, strips, etc. -- Fiction; Costume -- Comic books, strips, etc. -- Fiction; Neighborhoods -- Comic books, strips, etc. -- Fiction; Neighbors -- Comic books, strips, etc. -- Fiction; Bullies -- Comic books, strips, etc. -- Fiction; Monsters -- Comic books, strips, etc. -- Fiction; Foreign languages; Graphic novels; Adventure fiction